The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.7448/ias.17.4.19618
|View full text |Cite
|
Sign up to set email alerts
|

Stigma reduces and social support increases engagement in medical care among persons with HIV infection in St. Petersburg, Russia

Abstract: IntroductionThe proportion of people living with HIV (PLH) in care and on antiretroviral therapy (ART) in Russia is lower than in Sub-Saharan Africa [1]. This is undoubtedly due to a variety of systems and structural issues related to poor treatment access, linkage and care delivery models. However, little research has explored the reasons that PLH are not in care from their own perspectives. This information can help to guide the development of approaches for improving HIV care engagement in the country.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 0 publications
2
18
0
1
Order By: Relevance
“…Active outreach that encourages engagement in care ought to be enacted to connect these individuals to the HIV and drug treatment services they need to maximize their health and, potentially, protect that of their drug-using and sexual partners. Previous qualitative research with people with HIV in St. Petersburg has underscored the importance of perceived quality of medical staff/services and trust in one’s doctor as determinants of health service utilization [12]. Strengthening protocols to protect patients’ private health information within clinical care settings, communicating the value placed on such confidentiality to patients, and supporting patient–provider relationship-building over time through continuity of care may help to reduce the fears of confidentiality being breached and distrust of doctors commonly expressed as barriers to care by socially marginalized groups in Russia [12, 13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Active outreach that encourages engagement in care ought to be enacted to connect these individuals to the HIV and drug treatment services they need to maximize their health and, potentially, protect that of their drug-using and sexual partners. Previous qualitative research with people with HIV in St. Petersburg has underscored the importance of perceived quality of medical staff/services and trust in one’s doctor as determinants of health service utilization [12]. Strengthening protocols to protect patients’ private health information within clinical care settings, communicating the value placed on such confidentiality to patients, and supporting patient–provider relationship-building over time through continuity of care may help to reduce the fears of confidentiality being breached and distrust of doctors commonly expressed as barriers to care by socially marginalized groups in Russia [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Attitudinal studies in Russia have highlighted pervasive stigma directed toward both people with HIV [21–23] and people who inject drugs [24, 25] as well as the potential deterrent effect of HIV and drug stigmas on service utilization [12, 13, 2426]. Fear of confidentiality being breached and anticipated harm to personal and professional relationships are among the most common barriers to care reported by people with HIV in St. Petersburg [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experience of stigma may also be detrimental to the physical health of PLWH and interfere with their ability to manage the disease, including delayed or avoidance of HIV testing [22][23][24][25] and poor engagement in care [26,27]. A recent meta-analysis concluded that HIV-related stigma is associated with several physical health indicators, including AIDS-related symptoms, clinical stage of the disease, and self-reported physical health [17].…”
mentioning
confidence: 97%
“…The results of this study suggest that in the event that stigma reduces and there is an increase Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 12 June 2017in social engagement, the people will cope favourably with their conditions as earlier highlighted (Kelly et al, 2014). …”
Section: Discussionmentioning
confidence: 61%